Analysis of Pesona Dukcapil Application Service Quality on Population Administration Efficiency Using SERVQUAL - Fiteri, Fiteri; Kiswanto, Kiswanto (Komunitas Dosen Indonesia, 2026)
The digitalization of population administration services through e-government platforms has become a strategic priority; however, the alignment between user expectations and actual service performance remains insufficiently examined in developing country contexts. This study aims to evaluate the service quality of the Pesona Dukcapil web-based application using the SERVQUAL model and to explicitly examine its linkage to perceived administrative efficiency, operationalized through user-reported indicators of time–cost savings and service acceleration. A quantitative survey design was employed, utilizing a structured questionnaire with a five-point Likert scale administered to 44 purposively selected users, followed by gap analysis across ten indicators mapped to five SERVQUAL dimensions. The findings reveal consistently negative gap scores, with an overall average of -0.61; responsiveness exhibits the largest gap (-0.70), with response speed as the most critical deficit (-0.75), while tangibles show the smallest gap (-0.50). These results indicate systemic discrepancies between expectations and perceived performance. The study advances the literature by demonstrating that deficiencies in responsiveness and empathy dimensions are directly associated with reduced perceived administrative efficiency, thereby extending SERVQUAL beyond satisfaction-oriented evaluation toward operational outcome relevance. However, the cross-sectional design and limited sample size constrain the generalizability of the findings, suggesting cautious interpretation. The results provide a prioritized framework for improving digital public services, emphasizing system responsiveness, interface usability, and information clarity as key determinants of both service quality and administrative efficiency.